Relationship between hypertension and smoking: A preliminary study in South Kashmiri population of J&K - Gowher A. Wagai; Ubaid Jeelani; Mashkoor Ahmad Beg; Ghulam Jeelani Romshoo (Journal of Family Medicine and Primary Care)
Background: Smoking has been found to have a profound effect on mortality and cause-specific cardiovascular events in hypertension with significant interactions between the effects of smoking and hypertension and diabetes. Nevertheless, smoking is a major modifiable risk factor for cardiovascular disease (CVD). Materials and Methods: The present study was conducted on the patients visiting the medical Out Patient Department, Government Medical College (OPD GMC), Anantnag, for consultation with an aim to find whether smoking can be linked with CVD as a cause. A total of 304 patients were observed during this period for health check-ups. Results: The result reveals that 90% of male subjects across the age groups formulated in this study were in habit of smoking. In addition, 75% of female subjects across all age groups were also found to be in the habit of smoking. The majority of subjects including male subjects were potentially susceptible to CVD. The present prospective study was carried out to assess the role of smoking in causing hypertension and thereby various CVDs among the south Kashmiri population with high blood pressure levels in presence of high smoking rates. Discussions: Smoking acutely exerts a hypertensive effect, mainly through the stimulation of the sympathetic nervous system. Chronic smoking affecting arterial stiffness and wave reflection has greater detrimental effect on central blood pressure, which is more closely related to target organ damage than brachial blood pressure. Hypertensive smokers are more likely to develop severe forms of hypertension, including malignant and renovascular hypertension, an effect likely due to accelerated atherosclerosis. Conclusion: Smoking is potentially a leading cause of CVD among the South Kashmiri Population with high blood pressure levels in presence of high-smoking rates. Therefore, imperative measures regarding cessation of smoking are essential to prevent CVD which in line with clinical practice guidelines and policies should be emphasized to treat nicotine addiction in smokers by incorporating multicomponent and multilevel approaches for the better management of BP among the population studied.